The black reckoning [compact disc, unabridged] - Stephens, John, 1972- (Stephens, John, 1972- Books of beginning, 2015)
Emma has been kidnapped by the Dire Magnus, and siblings Kate and Michael go on a mission to rescue her. On top of that, Emma must locate the last of the magical Books of Beginning, the Book of Death, before the Dire Magnus does. As the fabric of time begins to fray, Emma becomes the final piece of the puzzle. Only if she can master the powers of this most dangerous book will they be able to save the world from the deadly final confrontation between magical and ordinary people.